2017
DOI: 10.1080/17843286.2017.1396676
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of Graves’ hyperthyroidism due to therapeutic biotin intervention

Abstract: Abnormal thyroid function tests in this euthyroid patient were found to be false due to significant interference of supraphysiological levels of plasma biotin. Laboratory tests applying immunoassays using a biotin-containing reagent should be interpreted with caution in patients on biotin substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Comparing TSH results detected on the old and new generation Elecsys TSH kit can be used as a new method to identify biotin interference. Previous reports showed that biotin can cause low TSH and lead to the wrong diagnosis of hyperthyroidism [15][16][17]. In our case, however, biotin caused high TSH level, contrary to previous reports.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparing TSH results detected on the old and new generation Elecsys TSH kit can be used as a new method to identify biotin interference. Previous reports showed that biotin can cause low TSH and lead to the wrong diagnosis of hyperthyroidism [15][16][17]. In our case, however, biotin caused high TSH level, contrary to previous reports.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, there are currently no reports on the interference of biotin with radioiodine uptake scans. Interestingly, our patient had mild symptoms consistent with hyperthyroidism while most patients with thyrotoxicosis due to biotin interference presented with minimal or no symptoms [4, 7, 8].…”
Section: Discussionmentioning
confidence: 88%
“…This immobilization system produces false positive results on standardized thyroid panel laboratory values. Lab results showing thyrotoxicosis in asymptomatic patients taking biotin have been reported in multiple cases [4]. However, results of radioactive iodine uptake (RAIU) scan while a patient is taking biotin are not well reported.…”
Section: Introductionmentioning
confidence: 99%
“…As luminescent label most often are used tris (2,2′-bipyridyl) ruthenium (II). Often, such analytical systems contain avidin-biotin reagents based on the capture ELISA principle and have a quite satisfactory bioanalytical characteristic, which brings opportunities for their wide practical use (De Roeck et al, 2017;Nie et al, 2017;Wang et al, 2017b).…”
Section: Methods For Detecting Of Systems Based On Mpsmentioning
confidence: 99%